PENGARUH METODE BERMAIN BERBANTUAN ALAT PERAGA PAPAN STIK TERHADAP KECERDASAN LOGIKA MATEMATIKA SISWA SEKOLAH DASAR - Fery Muhamad Firdaus; Khoirun Nisa (Jurnal Pendidik Indonesia (JPIn), 2018)
The purpose of this study is to determine the effect of the use of assisted play method sticks board props to the intelligence of mathematical logic of students of class II SDN 01 Curug Depok City on multiplication counting material. Sticker board props is one of the tools of mathematics that serves to facilitate students in calculating multiplication through concrete objects only by calculating the intersection. This research was conducted in class II SDN 01 Curug Kota Depok in the academic year 2017/2018. The method used in this research is quasi experimental method with research design of Two Group Randomized Subject Posttest Only. The sample in this study consisted of 20 experimental students and control class which amounted to 20 students. The results showed that students who were taught by using the method of playing assisted board props get the average value of mathematical logic intelligence of students is higher than the average value of mathematical logic intelligence of students who are taught without using the method of play assisted board props. Based on the data analysis can be seen the result of t test test posttest experimental class and control 0,008 with significance level 0,05. In addition, based on the calculation of effect test (effect size) obtained d value of 0.733. The value of the effect size obtained interprets that the use of assisted play method of sticks boards has an influence in the medium category. Thus, this shows that there is a moderate influence of the use of assisted play method of sticks on the mathematical intelligence of students in Class II SDN 01 Curug Kota Depok